Alpine skiing injuries: Causes and prevention - Bashir, S.; ul Haq Bhat, Z.; Dachenand, J.; Kumar, G. V. (International Journal of Yogic, Human Movement and Sports Sciences, 2019)
Snow skiing is the most popular winter Olympic sport. Skiing is an adventurous sport and has life taking risks associated with it. Proper precautions are a must for safeguarding one`s life while skiing. A skier must have a full-fledged knowledge about the injuries, their causes and preventive measures that can keep a skier safe. In this review we have tried to accumulate knowledge about the skiing injuries mainly based on alpine skiing to make the skiers aware of various injuries that can occur during skiing and preventive measures that can be taken to avoid these injuries. In the current review article, the major cause of injuries has been discussed along with their preventive measures. This study may be beneficial for alpine skiers.